Comparison of battery electromotive-force measurement and modelling approaches. (10th December 2022) - Hoekstra, F.S.J.; Raijmakers, L.H.J.; Donkers, M.C.F.; Bergveld, H.J.
Abstract: In this paper, different approaches for obtaining a battery Electromotive-Force (EMF) model, also referred to as Open-Circuit Voltage, are compared by experimentally measuring them and by subsequently applying different post-processing strategies, thus resulting in different EMF model realisations. The considered methods include GITT, interpolation of charge and discharge curves and extrapolation to zero current. The experiments are performed for two cells, namely a Lithium Nickel–Manganese–Cobalt (NMC) and a Lithium iron-Phosphate (LFP) cell. The accuracy of the EMF models is compared visually, as well as quantitatively in terms of voltage prediction accuracy using a linear parameter-varying overpotential model and SoC estimation accuracy using an extended Kalman filter. The results show that different methods excel at different performance indicators, for instance most accurate or least experiment time, but overall extrapolation to zero current has the best all-round performance. Highlights: Compares electromotive-force measurement and modelling approaches. Extensive review of the available methods. All methods are compared for two different cell chemistries. Pareto analysis of accuracy versus required measurement time.